Pengetahuan Pekerja Pengrajin Tempe Tentang Penggunaan Metode Terapi Latihan Model William Dan Kenzie Di Desa Pliken Kembaran Banyumas - Kuswati, Ani; Wahyudi,; Ratifah, (Jurnal Keperawatan Soedirman, 2008)
Appropriate body mechanics decrease the risk of injury musculoskeletal, case body movement, prevent fatigue and decrease the amount of energy that used. The purpose this research is to identify in-depth of the knowledge with in worker tempe makers about usage of exercise therapy WIilliam and Kenzie method and its benefit in Pliken Kembaran Banyumas. The research methodology used was qualitative research with phenomenology approach.Collecting data through in-depth interview with amount 5 participant. The result of research shows that knowledge with in worker tempe makers about exercise therapy very various, like understanding of exercise therapy, exercise therapy method and benefit its, caused by life experience factor, age, salary and information. Improve knowledge about usage of exercise therapy method and its benefit for worker tempe makers through counseling.